2018
DOI: 10.1159/000487178
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA GAS5 Represses Osteosarcoma Cells Growth and Metastasis via Sponging MiR-203a

Abstract: Background/Aims: LncRNA GAS5, a growth suppressor, has been reported to exert anti-tumor actions in various cancers, whereas the exact mechanism underling the anti-tumor action is still unclear. This study was aimed to investigate the effect of lncRNA GAS5 on osteosarcoma and tried to decode the underling mechanisms. Methods: Expressions of lncRNA GAS5 in MG-63 cells were silenced by shRNA transfection, while were overexpressed by vector transfection. Cell viability, migration, invasion and apoptosis were resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…In addition to activating PI3K pathway, some ncRNAs have been reported to inhibit the activity of PI3K signaling. lncRNA GAS5 expression is lower in tumor cells compared to normal cells; its over-expression inhibits tumor cell proliferation and migration while treatment with PI3K activator reduces the inhibitory effects [66][67][68][69][70][71][72]. Table 1 shows the examples of lncRNA that interact with PI3K signaling in different types of cancer.…”
Section: Non-coding Rna and Other Factors In Regulation Of Pi3k Pathwaymentioning
confidence: 99%
“…In addition to activating PI3K pathway, some ncRNAs have been reported to inhibit the activity of PI3K signaling. lncRNA GAS5 expression is lower in tumor cells compared to normal cells; its over-expression inhibits tumor cell proliferation and migration while treatment with PI3K activator reduces the inhibitory effects [66][67][68][69][70][71][72]. Table 1 shows the examples of lncRNA that interact with PI3K signaling in different types of cancer.…”
Section: Non-coding Rna and Other Factors In Regulation Of Pi3k Pathwaymentioning
confidence: 99%
“…However, lncRNAs can also play tumorigenic roles. GAS5 inhibited osteosarcoma cell growth and metastasis by targeting miR-203a [29]. And MRPL39 hindered the progression of gastric cancer via the direct interaction with miR-130 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that cytoplasmic lncRNAs generally function as ceRNAs to regulate mRNA expression via sponging versatile miRNAs, thereby playing a pivotal role in cancer metastasis (Lian et al , ; Shan et al , ; Sun et al , ; Wang and Kong, ; Yan et al , ). In fact, lncRNAs exert their functions in several biological processes via interaction with DNA, proteins, and RNAs, which is dependent on the subcellular localization of the lncRNAs within the cells to a large extent (Chen et al , ).…”
Section: Discussionmentioning
confidence: 99%